Semiconducting carbon nanotube fibers for electrochemical biosensor platforms. (July 2020) - Lee, Jin Yong; Cho, Dong-guk; Cho, Sung-Pyo; Choi, Jae-Hyuk; Sung, Sae Jin; Hong, Seunghun; Yu, Woong-Ryeol
Abstract: We report the fabrication of semiconducting single-walled carbon nanotube (sc-SWNT) fibers via wet-spinning for electrochemical biosensor platforms. SWNTs were purified using thermal and acid treatments and separated into metallic SWNTs and sc-SWNTs. The sc-SWNTs were then wet-spun into flexible fibers. Then, an enzyme capable of reacting with glucose was immobilized on the sc-SWNT fibers to investigate the utility of sc-SWNT fibers as an electrochemical biosensor platform. The enzyme-activated sc-SWNT fibers, which exhibited the field effects, were then configured into fiber-type glucose sensors capable of detecting the glucose in a solution, demonstrating the potential of sc-SWNT fibers as an electrochemical biosensor platform. Graphical abstract: Unlabelled Image Highlights: SWNTs were purified/separated into metallic/semiconducting SWNTs, and then wet-spun into free-standing flexible fibers. The fibers exhibited electrical conductivity of 70, 700 S/cm and tensile strength of 279 MPa and interestingly, field effects. This gate effect was demonstrated for a fiber-type glucose sensor with high sensitivity (0.5 μM).